2015
DOI: 10.1155/2015/142129
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Treatment Improves Learning-Memory Ability and Brain Glucose Metabolism in a Mouse Model of Alzheimer’s Disease: Using Morris Water Maze and Micro-PET

Abstract: Introduction. Alzheimer's disease (AD) causes progressive hippocampus dysfunctions leading to the impairment of learning and memory ability and low level of uptake rate of glucose in hippocampus. What is more, there is no effective treatment for AD. In this study, we evaluated the beneficial and protective effects of electroacupuncture in senescence-accelerated mouse prone 8 (SAMP8). Method. In the electroacupuncture paradigm, electroacupuncture treatment was performed once a day for 15 days on 7.5-month-old S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 37 publications
3
35
0
Order By: Relevance
“…It was shown that senescence-accelerated mouse (SAMP8), as a model of aging, displays many features known to occur in the early stage of AD such as increased oxidative stress, amyloid-beta level alteration, and tau phosphorylation [12]. What is more, published data [13] and our previous research [5] demonstrated that SAMP8 could undergo acupuncture therapy to improve learning and memory ability. In this study, therefore, SAMP8 mice were selected as an ideal animal model for Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was shown that senescence-accelerated mouse (SAMP8), as a model of aging, displays many features known to occur in the early stage of AD such as increased oxidative stress, amyloid-beta level alteration, and tau phosphorylation [12]. What is more, published data [13] and our previous research [5] demonstrated that SAMP8 could undergo acupuncture therapy to improve learning and memory ability. In this study, therefore, SAMP8 mice were selected as an ideal animal model for Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%
“…This therapy has been applied for AD treatment and could improve the cognitive function [26] and brain energy metabolism [5, 27]. Therefore, EA is considered an effective therapeutic intervention for AD [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There exists some indivisible relations between Governor Vessel (GV) and brain, both in distribution and in function. Clinical and experimental studies have shown that acupuncture at GV possessed therapeutic effects in AD treatment (Yang et al, 2013; Jiang et al, 2015; Wang et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…2a). The shortest possible time to find the platform is interpreted as a better learning and memory21. We found no difference of spatial learning and memory between WT mice and PAFR −/− mice in MWM task (Fig.…”
Section: Resultsmentioning
confidence: 68%